Osteoinductivity and biomechanical assessment of a 3D printed demineralized bone matrix-ceramic composite in a rat spine fusion model. (June 2021) - Plantz, Mark A.; Minardi, Silvia; Lyons, Joseph G.; Greene, Allison C.; Ellenbogen, David J.; Hallman, Mitchell; Yamaguchi, Jonathan T.; Jeong, Soyeon; Yun, Chawon; Jakus, Adam E.; Blank, Kenneth R.; Havey, Robert M.; et al.
Abstract: We recently developed a recombinant growth factor-free bone regenerative scaffold composed of stoichiometric hydroxyapatite (HA) ceramic particles and human demineralized bone matrix (DBM) particles (HA-DBM). Here, we performed the first pre-clinical comparative evaluation of HA-DBM relative to the industry standard and established positive control, recombinant human bone morphogenetic protein-2 (rhBMP-2), using a rat posterolateral spinal fusion model (PLF). Female Sprague–Dawley rats underwent bilateral L4-L5 PLF with implantation of the HA-DBM scaffold or rhBMP-2. Fusion was evaluated using radiography and blinded manual palpation, while biomechanical testing quantified the segmental flexion-extension range-of-motion (ROM) and stiffness of the fused segments at 8-weeks postoperatively. For mechanistic studies, pro-osteogenic gene and protein expression at 2-days and 1-, 2-, and 8-weeks postoperatively was assessed with another cohort. Unilateral fusion rates did not differ between the HA-DBM (93%) and rhBMP-2 (100%) groups; however, fusion scores were higher with rhBMP-2 ( p  = 0.008). Both treatments resulted in significantly reduced segmental ROM ( p  < 0.001) and greater stiffness ( p  = 0.009) when compared with non-operated controls; however, the degree of stabilization was significantly higher with rhBMP-2 treatment relative to the HA-DBM scaffold. In the mechanistic studies, PLGA and HA scaffolds were used as negative controls. Both rhBMP-2 and HA-DBM treatments resulted in significant elevations of several osteogenesis-associated genes, including Runx 2, Osx, and Alp. The rhBMP-2 treatment led to significantly greater early, mid, and late osteogenic markers, which may be the mechanism in which early clinical complications are seen. The HA-DBM scaffold also induced osteogenic gene expression, but primarily at the 2-week postoperative timepoint. Overall, our findings show promise for this 3D-printed composite as a recombinant growth factor-free bone graft substitute for spinal fusion. Statement of significance: Despite current developments in bone graft technology, there remains a significant void in adequate materials for bone regeneration in clinical applications. Two of the most efficacious bone graft options are the gold-standard iliac crest bone graft and recombinant human-derived bone morphogenetic protein-2 (rhBMP-2), available commercially as Infuse™. Although efficacious, autologous graft is associated with donor-site morbidity, and Infuse™ has known side effects related to its substantial host inflammatory response, possibly associated with a immediate, robust osteoinductive response. Hence, there is a need for a bone graft substitute that provides adequate osteogenesis without associated adverse events. This study represents a significant step in the design of off-the-shelf growth factor-free devices for spine fusion. Graphical abstract: Image, graphical abstract